ANALYSIS OF VOCABULARY USAGE IN THE ANIMATED FILM 'TOY STORY I' AS A MEANS OF ENHANCING ENGLISH PROFICIENCY IN CHILDREN - Ridwan Ghozali; Yousef Bani Ahmad; Dedeh Kartini (IKIP Siliwangi, 2024)
This study employs qualitative content analysis to explore the diverse vocabulary usage within the animated film